Seabirds as monitors of marine plastic pollution - Perold, Vonica (Department of Biological Sciences, 2025)
Small buoyant plastic items are one of the most pervasive and abundant marine pollutants. They pose significant environmental impacts, including threatening the health of marine life through plastic ingestion, necessitating efforts to reduce plastic leakage into the sea. To evaluate the effectiveness of mitigation strategies, it is essential to understand trends in marine plastic densities, types, and sources, which requires a reliable baseline for repeated assessments. While sea-surface net trawls are commonly used to monitor trends in small floating plastics at sea, they face several challenges. Seabirds, particularly petrels and albatrosses (order Procellariiformes), offer a practical alternative to net sampling as they often ingest and retain buoyant plastics encountered while foraging at sea, making them valuable indicators of this type of plastic pollution. However, few studies have thoroughly tested their utility. Larger species, such as albatrosses and giant petrels, typically ingest macroplastics items like bags, bottle lids, and fishery-related debris, which can often be traced back to specific sources. In contrast, smaller petrels, including storm petrels, prions, and shearwaters, tend to ingest smaller items like industrial pellets and fragments of larger plastic objects, whose sources are more challenging to identify. Due to their high propensity for ingesting plastics and their tendency to consume larger volumes, these smaller petrels may be particularly well- suited for monitoring ingested plastic loads over time. In Chapter 2, I assess trends in litter items collected at the nests of albatrosses and giant petrels breeding on Marion Island in the southwestern Indian Ocean, from 1996 to 2018. Temporal variation in litter composition and amounts were compared to data on Patagonian toothfish Dissostichus eleginoides fishing intensity in the area. Fishery-related litter abundance peaked during industry's height, declining in the following two decades. Other litter items increased over the last decade, when the most frequently recorded identifiable litter items were drink bottle lids from Indonesia. Long-distance drift of buoyant plastic items from Southeast Asia, mainly Indonesia, is a major source of litter to the western Indian Ocean. In Chapter 3, I assess the use of an indirect method to sample plastics ingested by seabirds by examining regurgitated Brown Skua Catharacta antarctica (Stercorariidae) pellets containing prey remains of petrels at Inaccessible Island in the central South Atlantic Ocean. I compare the size of plastics in skua pellets to those collected directly from seabird carcasses, to assess the validity of this method. I also compare the composition of plastics ingested within each seabird taxon to small buoyant plastics sampled with a neuston net, to understand how the ingested plastic compares with that found in the environment. I found that as a community, petrels reflected the composition of small buoyant plastics at sea, providing support for their use as biomonitors of marine plastic pollution. In Chapter 4, I assess how plastic loads in four petrels have changed from 1987 to 2018 in roughly decadal time periods and years. More than 3 700 regurgitated Brown Skua pellets, each containing the remains of a single petrel, indicated fluctuations in plastic loads between periods and years, but no overall clear trend was evident in any species. The number and proportions of industrial pellets among ingested plastics decreased over the study period, indicating that industry initiatives to reduce pellet leakage have been at least partly successful. In Chapter 5, I assess whether the size, mass, and polymer types of ingested plastic items have changed over the study period (1987 – 2018) to help interpret the results from Chapter 4. I found little change in the size and mass of ingested plastics since the 1980s. The ratio of polypropylene to polyethylene has increased consistently among hard fragments of user items over time. Overall, the limited change in plastic characteristics is consistent with the absence of clear trends in plastic loads over time (Chapter 4). In Chapter 6, which also serves as my synthesis, I investigate whether plastics sampled on beaches along the southern Cape coastline of South Africa from 1984 to 2023 exhibit the same trends in composition as small buoyant plastics ingested by petrels from 1987 to 2018. The findings show minimal changes in beached hard fragment sizes, with a recent increase in industrial pellet mass due to two major spills at sea off South Africa in 2017 and 2020. Polymer ratios in hard fragments mirrored those ingested by seabirds in the South Atlantic, indicating common influencing variables. More data are needed to understand the increase in the ratios of polypropylene to polyethylene over time, and how this may influence retention rates of plastics on the sea surface. In summary, this thesis demonstrates that sampling plastics ingested by seabirds provides a comprehensive assessment of marine litter composition and sources. Seabirds offer valuable insights into temporal trends in plastic loads and characteristics which align with variations observed in beached plastics. The lack of clear patterns in plastic loads over time suggests that initiatives to reduce the influx of plastics, and remove existing litter, may be preventing a rapid increase in the density of floating plastics at sea, despite the ongoing increase in global plastic production. However, the possible egestion of plastics by seabirds while out at sea, may also account for the lack of clear trends. More empirical data are needed to assess this, and how turnover rates of floating plastics will change under different plastic emission scenarios, to help interpret patterns in the loads and sizes of plastics in the marine environment. These insights are crucial for assessing the efficacy of mitigation strategies to reduce plastic waste leakage into the marine environment.